2010
DOI: 10.1590/s0103-84782010000800021
|View full text |Cite
|
Sign up to set email alerts
|

Patogenicidade de Beauveria bassiana sobre estágios imaturos de Stomoxys calcitrans

Abstract: RESUMOPor ser um díptero hematófago, a mosca Stomoxys calcitrans (Linnaeus, 1758)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Many studies showed that the stable fly is susceptible to entomopathogenic fungi under laboratory conditions (e.g. Watson et al, 1995;Moraes et al, 2010;López-Sánchez et al, 2012), but there are only a few reports on the efficacy of fungi under natural infestation conditions. For example, aqueous spore formulation of M. anisopliae applied directly on cows reduced natural infestation by S. calcitrans up to 73% (Cruz-Vazquez et al, 2015).…”
Section: Treatment Of Stables With B Bassiana Sporesmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies showed that the stable fly is susceptible to entomopathogenic fungi under laboratory conditions (e.g. Watson et al, 1995;Moraes et al, 2010;López-Sánchez et al, 2012), but there are only a few reports on the efficacy of fungi under natural infestation conditions. For example, aqueous spore formulation of M. anisopliae applied directly on cows reduced natural infestation by S. calcitrans up to 73% (Cruz-Vazquez et al, 2015).…”
Section: Treatment Of Stables With B Bassiana Sporesmentioning
confidence: 99%
“…early May) and should be repeated during the summer due to the relatively short viability of fungal spores under field conditions. Secondary effects of entomopathogenic fungi on flies by inhibiting oviposition and infecting eggs have also been documented (Moraes et al, 2010(Moraes et al, , 2014Baleba et al, 2021), which may also contribute to the reduction of population growth.…”
Section: Treatment Of Stables With B Bassiana Sporesmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to 90% mortality was demonstrated in adult stable flies exposed to B. bassiana [223]. Moreas et al [227] showed pathogenicity of B. bassiana to immature stages of stable flies. Watson et al [228] showed that B. bassiana helped control stable flies in the sawdust bedding in calf hutches, whilst Oliveira et al [229] demonstrated the use of this fungus in controlling insect pests in poultry production.…”
Section: Entomopathogenic Fungimentioning
confidence: 99%
“…Running applied research, which includes biological control (MORAES et al, 2008(MORAES et al, , 2010, population monitoring, and chemical control, should lead to the identification of potentially useful alternatives for controlling the parasite and preventing outbreaks. Unfortunately, such alternatives are not yet available and more time is required for their development before they can be applied in practice.…”
Section: Challenges and Outlookmentioning
confidence: 99%